PROSPEK INOVASI PENGELOLAAN SAMPAH SEBAGAI STRATEGI MITIGASI PEMANASAN GLOBAL DI KOTA MAGELANG - Arifin, Mohamad Zaenal (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2019)
The waste sector contributes GHG to the atmosphere, especially from landfills, the existing waste contributes 3-4% of global GHG emissions. This study aims to calculate the potential of methane gas emissions generated from waste and identify innovative strategies to mitigate the impact on global warming caused by methane gas emissions. This research method was built using the literature study approach. Data collection in this study was carried out using secondary data from the publication of technical agencies such as population data, volume of waste and technical data on waste management in the city of Magelang. Meanwhile, the processing techniques and data analysis in this study with descriptive analysis to describe the projections of methane gas emissions theoreticallyThe results show that with the population of Magelang City in 2017 as many as 130,857 people produced waste generation of 61,613.8 tons / year. Based on the amount of waste generation, using the mass balance calculation from the decomposition of municipal waste aerobically and anaerobically according to Solvato's formula produces the potential for methane gas emissions of 3.943, 28 tons / year CH4. The amount isprojected to continue to rise for the next 10 (ten) years in proportion to the population. Waste management innovation as a strategy to mitigate the effects of global warming in the Magelang city can be pursued through organic villages, waste banks, TPS 3R and TPST, bioconversion of organic waste with maggot from black soldier fly, utilization of waste in landfill as Biogas, conversion of potential of waste landfill biomass into electrical energy.